Isolated and combined effects of soil salinity and waterlogging in seedlings of 'Green Dwarf' coconut - Wiliana Júlia Ferreira de Medeiros (Semina: Ciências Agrárias, 2018)
Soil salinization is a problem commonly found in semi-arid regions. In addition, the problem of salinity is aggravated in clayey soils when accompanied by cycles of waterlogging in the rainy season or when excess irrigation is applied. In this work we evaluated the isolated and combined effects of soil salinity and waterlogging on the responses of young plants of ‘Green Dwarf’ coconut. The experiment was conducted under controlled environment in a complete randomized block design, arranged in split plots with five replications. The plots comprised five waterlogging cycles (0, 1, 2, 3 and 4), each with a duration of four days, and applied at 30, 60, 90 and 120 days into the experimental period, with the sub-plots consisting of five levels of soil salinity (1.70, 11.07, 16.44, 22.14 and 25.20 dS m-1). Response of coconut seedlings to waterlogging was dependent on the level of soil salinity, with waterlogging significantly impairing biomass accumulation and leaf expansion at low soil salinity levels, but causing no additional harm at elevated salinity. Leaf gas exchange was reduced mainly due to soil salinity, and this response was related to stomatal and non-stomatal effects. Seedlings of ‘Green Dwarf’ coconut used in this study were classified as moderately-tolerant to salinity when grown in soils with an electrical conductivity up to 11.07 dS m-1, having the potential to be used in revegetation programs of salt-affected areas, provided that these areas are not exposed to frequent waterlogging cycles.